Responda:
Por favor, consulte A explicação.
Explicação:
# "Pré-requisito:" P (AuuB) = P (A) + P (B) -P (AnnB) …. (estrela) #.
#P (AuuBuuC) = P (AuuD), "onde" D = BuuC #, # = P (A) + P (D) -P (AnnD) ………. porque, (estrela) #, # = P (A) + cor (vermelho) (P (BuuC)) - cor (azul) (P Ann (BuuC)) #, # = P (A) + cor (vermelho) (P (B) + P (C) -P (BnnC)) - cor (azul) (P (AnnB) uu (AnnC)), #
# = P (A) + P (B) + P (C) -P (BnnC) -cor (azul) {P (AnnB) + P (AnnC) -P ((AnnB) nn (AnnC) #, # = P (A) + P (B) + P (C) -P (AnnB) -P (BnnC) -P (AnnC) + P (AnnBnnC), #
como desejado!